Friend effects framework: Contrastive and hierarchical processing in cheerleader effects - Edwin Burns (Cognition, 2021)
Cheerleader effects, group attractiveness effects, and divisive normalization are all characterized by faces appearing more attractive when seen within a group. However, it is possible that your friends could have a detrimental effect upon your attractiveness too: if these group effects arose partly as a contrastive process between your face and your friends, then highly attractive friends may diminish your attractiveness. We confirm this hypothesis across two experiments by showing that the presence of highly attractive friends can indeed make you appear less attractive (i.e., a reverse cheerleader effect), suggesting friend effects are driven in part by a contrastive process against the group. However, these effects are also influenced by your own attractiveness in a fashion that appears consistent with hierarchical encoding, where less attractive targets benefit more from being viewed in an increasingly unattractive group than attractive targets. Our final experiment demonstrates that the company of others not only alters our attractiveness, but also induces shifts in how average or distinctive a target face appears too, with these averageness effects associated with the friend effects observed in our first experiment. We present a Friend Effects Framework within which ‘friend effects’ is an umbrella term for the positive (e.g., cheerleader effects, group attractiveness effects) and negative (i.e., the reverse cheerleader effect) ways in which hierarchical encoding, group contrastive effects, and other influences of friends can have on your attractiveness.